FLEXIBLE BRONCHOSCOPY RESULTS IN NGHE AN OBSTETRICS AND GYNECOLOGY HOSPITAL FROM JANUARY 2018 TO SEPTEMBER 2019 (Vietnam Journal of Community Medicine, 2022)
Objective: From January 2018 to September 2019, the results of flexible bronchoscopy in children with respiratory illnesses at Nghe An Obstetrics and Gynecology Hospital were evaluated. Methods and subjects: The Intensive Care Unit - Poison Control Department, Nghe An Obstetrics and Pediatrics Hospital conducted a retrospective and prospective study with convenient sampling on 23 patients with respiratory disorders who were scheduled for bronchoscopy. Results: Airway mucositis was seen in 47.8%, airway malformation in 21.7 percent, bronchial purulent inflammation in 21.7 percent, bronchial obstructions in 4.4 percent, and lobar hemorrhage in 4.4 percent. Bronchoalveolar lavage revealed 30.4 percent microbial etiology, with 17.4 percent of bacterial infections, 8.7 percent of fungal infections, and 4.3 percent of respiratory syncytial virus (RSV) infections. During and after endoscopic treatments, 17.4% of patients experienced temporary hypoxia. Conclusion: Flexible bronchoscopy is a valuable and safe diagnostic tool in children for respiratory illnesses.
Keywords: Bronchoscopy, respiratory diseases, children.